Analisis Implementasi Kurikulum Merdeka di Sekolah Penggerak Kabupaten Garut : Studi Kasus SMAN 8 Garut dan SMAN 15 Garut - Tita Latifah Munawaroh; Arneta; Gita; Reiva; Santi; Yopi (PANDU : Jurnal Pendidikan Anak dan Pendidikan Umum, 2025)
This study aims to explore the implementation of the Kurikulum Merdeka (Independent Curriculum) in two pilot schools in Garut Regency, namely SMAN 8 Garut and SMAN 15 Garut. Using a qualitative descriptive approach, data were collected through interviews, observations, and document studies. The results indicate that both schools faced challenges in adopting the new curriculum, such as the need for teacher training and student adaptation to more active learning methods. However, the implementation of the Kurikulum Merdeka has shown significant positive impacts, especially in project-based learning (P5) that enhances creativity, teamwork, and critical thinking skills among students. Teachers also gained more flexibility in designing learning processes, leading to a more engaging classroom atmosphere. This study provides recommendations focusing on increasing teacher training, developing more systematic curriculum implementation guidelines, and providing adequate infrastructure support to ensure sustainable implementation.